The Effect of Dental Paste from Coconut Butter as a Replacement to Toothpaste on Reducing Debris Index and Plaque Index in Class 3 to 5 Students in Elementary School - Mardiati, Erni; Rikawarastuti, Rikawarastuti; Wiradona, Irmanita (Open Access Macedonian Journal of Medical Sciences, 2022)
The coconut tree is a multipurpose plant because all parts of it, from the roots to the coconut fruit, can be used for clothing, food and shelter. Coconut fruit contains calories, water, protein, carbohydrates, fat, calcium, iron, vitamins A, B and C as well as edible parts. Besides being processed into coconut oil (coconutoil) it also contains many benefits for human health, coconut can also be processed into Coconut Butter which can be made as toothpaste. Many elementary school age children still have dirty teeth in their oral cavity up to 67.3%. Therefore, researchers want to know the effect of toothpaste from coconut butter as a substitute for toothpaste on the reduction of index debris and index plaque in students in grades 3 to 5 in elementary schools.This type of research uses Quasi Experiment (Pseudo Experiment). The research design used a pre-test and post-pest approach. Pre-test. The samples in this study were 32 grade 3 students, 34 grade 4 students and 34 grade 5 students, so the total number of students was 100 students. Sampling using purposive sampling technique, and statistical tests using the Wilcoxom test. The results showed that the debris index before brushing teeth using coconut batter as a substitute for toothpaste obtained an average value of 1.8, while for the debris index after brushing teeth using coconut batter as a substitute for toothpaste, the average value was 0.4. Judging from the p Value = 0.000, the probability is smaller than 0.05 (p <0.05), so H0 is rejected and H1 is accepted, thus these results indicate that there is a significant difference between the debris index before brushing teeth using coconut batter as a substitute for toothpaste. and index debris after brushing teeth using coconut batter as a substitute for toothpaste. Plaque index before brushing teeth using coconut batter as a substitute for toothpaste obtained an average value of 4.4, while for the index plaque after brushing your teeth using coconut batter as a substitute for toothpaste, the average value is 2.4. Judging from the p value = 0.000, the probability is smaller than 0.05 (p <0.05), so H0 is rejected and H1 is accepted, thus these results indicate that there is a significant difference between the plaque index before brushing your teeth using coconut batter as a substitute for toothpaste. and index plaque after brushing your teeth using coconut batter as a substitute for toothpaste